Utilizing the Picture Describing Strategy for Enhancing Speaking Skills in Teaching - Sarmila, Sarmila; Murtiningsih, Tenny; Pebriano, Nor Angga; Aflahah, Noor Aida; Samsuri, Muhammad; Farid, Muhammad Rifa’at Adiakarti; Kurniaji, Ganno Tribuana (Universitas Muhammadiyah Surakarta, 2023)
This research focuses on exploring the effectiveness of the Describing Picture Strategy in teaching speaking skills to students. The study aims to enhance students' English-speaking abilities by employing visual aids such as pictures during the learning process. The qualitative research design was utilized, and data were collected through interviews and observations with an English teacher at SMK Muhammadiyah 1 Banjarmasin. The findings demonstrate that using pictures as speaking prompts can improve pronunciation, vocabulary retention, and overall language confidence. Additionally, picture-based activities engage students and create a more enjoyable learning experience. The study recommends that English teachers integrate the Describing Picture Strategy in their teaching approaches to foster active classrooms and enhance students' interest and proficiency in speaking English. However, the research acknowledges the need for further investigation to address certain limitations and refine the strategy for optimal results.